Comparison of water pumping between pump driven by wind mill and electric motor into Brazil - Pedroso, T. C. [UNESP]; Souza, T. M. [UNESP] (My University, 2014)
The proposed work consists in the comparison of the application of two systems for the pumping of water. With a pump drive by electric motor and the other by wind mill, in order to demonstrate the efficiency and pay-back of each system. The installation of both projects is simple, having only that consider the lifting height of water for the application of each system, and in the case of using the wind mill, must also be taken into account the average wind speed and the availability of daily even. For the comparison between the two systems presented, became the pumping for a volume of 72,000 liters of water per day, to the heights of 10, 50, 100 and 150 meters, during 6 hours by day and it took into account the price of the installation of the two systems and the cost of electrical energy for the case of pumping with electric motor. Through the calculations performed, it was found that the installation of wind mill have quicker pay back from the heights of 100m, around four years and 150m around two years, in comparison with the electric motor. Life time the systems is 20 years.
Keywords: Electrical motor; Pumping of water; Wind mill